The Influence of Benefits, Convenience and Risk on Interest in Using Dana Applications (Case Study of Students at the Faculty of Economics, Samudra University) - Fitri, Anisa; Fuad, Muhammad; Setianingsih, Dias (Transforma Jurnal Manajemen, 2024)
This research aims to determine the influence of benefits, convenience and risks on interest in using the DANA application (case study of students at the Faculty of Economics, Samudra University). The population in this study were active students at the Faculty of Economics, Samudra University for the 2019 to 2022 academic year, totaling 973 people and a sample of 283 people using a purposive sampling technique by determining the sample size using the Slovin formula. The data analysis method in this research uses multiple linear regression analysis, t test, F test and coefficient of determination. The constant value ? is 2.309. The regression coefficient for the variables benefit, convenience and risk shows a positive influence on the variable of interest in using the DANA application. Benefits, convenience and risks partially have a significant effect on interest in using the DANA application. Benefits, convenience and risks simultaneously have a significant influence on interest in using the DANA application. Adjusted R2 is 0.449. This means that the variables of benefit, convenience and risk influence interest in using the DANA application by 44.9%, while the remaining 55.1% is influenced by other variables outside this research model.